Reduction of bladder activity on FDG PET/CT scan in patients with urinary bladder carcinoma - Tsai, S.-C.; Ou, Y.-C.; Cheng, C.-L.; Li, J.-R.; Lin, Y.-C.; Ho, H.-C.; Chiu, K.-Y.; Su, C.-K.; Lin, W.-Y. (Nuklearmedizin - NuclearMedicine, 2015)
Oral hydration with large volume of fluid, high dose of diuretics and maximum bladder distension are frequently required to achieve an adequate urinary FDG clearance in an FDG PET/CT protocol for bladder cancer or pelvic tumour evaluation. Although most patients tolerated these procedures for eliminating urinary FDG activity, these procedures may be still unpleasant. Aim: Is there a more patient-friendly protocol which is less burdensome and yet provides a satisfactory FDG clearance in urine? In this study, we established a patient-friendly FDG PET/CT protocol without compromising urinary FDG clearance. Patients, methods: 23 patients with biopsy-proven urinary bladder cancers were recruited to evaluate the effectiveness of this patient-friendly protocol on reducing urinary bladder FDG activity. The patient-friendly protocol includes encouraging patients to take a tolerable amount of fluid, delaying the administration of low dose diuretic, shortening the urine holding time and using delayed imaging. Results: All of the patients tolerated this patient-friendly procedure well. In addition, the patient-friendly protocol was effective in reducing FDG activity in the urine. One hundred percent of primary bladder cancer were visualized on the FDG PET/CT images using this patient-friendly protocol. Conclusions: This patient-friendly FDG PET/CT protocol is less intrusive yet effective in reducing urinary FDG activity.
Keywords: Bladder cancer; FDG PET/CT; urinary FDG activity; protocol